The Economic Impact of Human Resource Management Practices on Organizational Performance in Manufacturing Companies in West Java - Fitria Dewi Santosa (Generasi Sains Indonesia, 2025)
This study investigates the connection between organizational performance and human resource management (HRM) practices in West Java, Indonesian manufacturing firms. It specifically looks at how employee engagement, performance management, training and development, and recruitment processes affect the overall performance of the company. Data were gathered from 150 workers at a variety of manufacturing companies in the area using a quantitative study design. The findings demonstrate that HRM approaches significantly and favorably affect organizational performance, especially employee engagement, training and development, and performance management. Training and development were found to be the next most important aspect, after employee involvement. The study indicates that by strategically implementing HRM strategies that support employee involvement, skill development, and efficient performance management, firms in West Java can improve their performance. These results underline the significance of human capital as a primary driver of competitive advantage and organizational performance, supporting the resource-based view of HRM.